2018
DOI: 10.12659/msm.911308
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Antibiotic-Associated Diarrhea in Critically Ill Patients

Abstract: BackgroundWe analyzed the factors related to AAD to inform the rational use of antibiotics in critically ill patients and to reduce the incidence of AAD by providing a reference for antibiotic use in the clinical setting.Material/MethodsThis study was a retrospective analysis of the clinical data of patients who were hospitalized in the ICU of the First Teaching Hospital of Xi’an Jiaotong University from January 1, 2015 to December 31, 2016. Patients with AAD were assigned to the case group, and all others wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 32 publications
4
40
0
5
Order By: Relevance
“…3,5,28,29 AAD is especially more likely to occur when these are combined with other antibiotics. 2 Our study showed that the use of azithromycin and enzyme inhibitors was associated with AAD in ICU patients receiving antifungals, which is consistent with the literature. 2 Our study also showed that the antifungal treatment time was associated with AAD in ICU patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…3,5,28,29 AAD is especially more likely to occur when these are combined with other antibiotics. 2 Our study showed that the use of azithromycin and enzyme inhibitors was associated with AAD in ICU patients receiving antifungals, which is consistent with the literature. 2 Our study also showed that the antifungal treatment time was associated with AAD in ICU patients.…”
Section: Discussionsupporting
confidence: 92%
“…13,16 The duration of ICU admission (17.88 ± 11.11 vs. 9.44 ± 6.68 days) was significantly lower in the no AAD group (P < 0.001), indicating that the occurrence of AAD could prolong the duration of ICU admission of critically ill patients. However, there was no significant difference in mortality between these two groups, and although this is consistent with our previous study, 2 it is not consistent with previous reports in the literature. This may be influenced by specific customs in different parts of China; for example, in rural areas around Shaanxi, many families request discharge of critically ill patients while they are still alive.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations